2007
DOI: 10.1007/s00198-006-0306-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced prediction of fracture risk combining vertebral fracture status and BMD

Abstract: These findings indicate that at any given BMD T-score, the risk of incident vertebral, non-vertebral, and any fracture depended heavily on prevalent radiographic vertebral fracture status. Assessment of vertebral fracture status, in addition to BMD, provides practical and relevant clinical information to aid in predicting fracture risk in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(113 citation statements)
references
References 28 publications
8
93
0
7
Order By: Relevance
“…For any given BMD T-score, the risk of an incident vertebral, non-vertebral fragility, and any fracture differs by up to twelve times, two times, and seven Six patients with X-ray unsuitable for evaluation not included a Not walking for >4 weeks in the last year b Rating based upon clinical judgment Fig. 1 DXA + T-score<−2.5, DXA − T-score≥−2.5, X-ray + vertebral fracture present, X-ray − no vertebral fracture present times, respectively, when information regarding spine fractures is considered [13]. Even when corrected for BMD, prevalent vertebral fractures increase the risk of future fracture up to fivefold [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For any given BMD T-score, the risk of an incident vertebral, non-vertebral fragility, and any fracture differs by up to twelve times, two times, and seven Six patients with X-ray unsuitable for evaluation not included a Not walking for >4 weeks in the last year b Rating based upon clinical judgment Fig. 1 DXA + T-score<−2.5, DXA − T-score≥−2.5, X-ray + vertebral fracture present, X-ray − no vertebral fracture present times, respectively, when information regarding spine fractures is considered [13]. Even when corrected for BMD, prevalent vertebral fractures increase the risk of future fracture up to fivefold [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, the most common and typical osteoporotic fractures, these of the vertebrae, are mainly asymptomatic. Yet, radiologically diagnosed vertebral deformities are associated with deterioration of certain aspects of the quality of life of the patients and numerous studies, confirmed by meta-analysis, have shown them to be strong, independent determinants of new osteoporotic fractures at several skeletal sites, including the hip [13,16,17]. Despite these and the efficacy of antiosteoporotic medications in patients with vertebral deformities, current case-finding strategies do not include spine radiographs in the selection of patients for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such fractures changes the clinical diagnosis to osteoporosis and has a significant impact on treatment decisions. Moreover, fracture risk increases as vertebral fractures increase in number and severity [33].…”
Section: Resultsmentioning
confidence: 99%
“…This is perhaps not surprising given that the patients investigated had a non-vertebral fracture which triggered FLS assessment. However, incorporation of VFA into FLS protocols has the potential to reveal two sub-groups of non-vertebral fracture patients that may be managed differently as a result of ascertainment of vertebral fracture status: [55]. These investigators concluded:…”
Section: Secondary Fracture Preventionmentioning
confidence: 99%